North Sumatra Economic Growth Analysis - Ella Silvana Ginting; Apren Halomoan Hutasoit; Naca Peranginangin (Jurnal Mantik, 2021)
This research was conducted with the aim of knowing the effect of exports, imports and unemployment on North Sumatra's GRDP. This type of research is a quantitative study with a quantitative descriptive approach. This research was conducted by utilizing data obtained from the Central Bureau of Statistics. The sample of this research is 33 districts and cities in North Sumatra for the period 2017 and 2018. In this study, the analysis technique used is to regress panel data so as to produce multiple linear regression analysis. From the results of hypothesis testing, it is found that exports do not have a significant effect on GRDP of North Sumatra. Hypothesis test results also show that imports do not have a significant effect on the GRDP of North Sumatra. Furthermore, unemployment also does not have a significant effect on North Sumatra's GRDP. The contribution to GRDP through exports, imports and unemployment was 8.12%, while the rest was generated by other variables not examined in this study.